Pharmacological and Psychological Treatment Have Common and Specific Effects on Brain Activity in Obsessive-Compulsive Disorder - van der Straten, Anouk; Bruin, Willem; van de Mortel, Laurens; ten Doesschate, Freek; Merkx, Maarten J. M.; de Koning, Pelle; Vulink, Nienke; Figee, Martijn; van den Heuvel, Odile A.; Denys, Damiaan; van Wingen, Guido (Depression and Anxiety, 2024)
Initial treatment for obsessive-compulsive disorder (OCD) consists of pharmacological treatment with selective serotonin reuptake inhibitors (SSRIs) and/or psychological treatment with cognitive behavioral therapy (CBT). The assumption is that both treatments have different neural working mechanisms, but empirical evidence is lacking. We investigated whether these treatments induce similar or different functional neural changes in OCD. We conducted a longitudinal nonrandomized controlled trial in which thirty-four OCD patients were treated with sixteen weeks of CBT or SSRIs. Functional magnetic resonance imaging was performed before and after treatment during emotional processing (emotional face matching and symptom provocation tasks) and response inhibition (stop signal task). Twenty matched healthy controls were scanned twice with a similar time interval. Both CBT and SSRIs were successful in reducing OCD symptoms. Compared to healthy controls, treatment led to a reduction of insula activity in OCD patients during symptom provocation. The comparison between treatment groups revealed widespread divergent brain changes in the cerebellum, posterior insula, caudate nucleus, hippocampus, and occipital and prefrontal cortex during all tasks, explained by relative increases of activity following CBT compared to relative decreases of activity following SSRIs. Pharmacological and psychological treatment primarily lead to opposite changes in brain function, with a common reduction of insula activity during symptom provocation. These findings provide insight into common and specific neural mechanisms underlying treatment response, suggesting that CBT and SSRIs support recovery from OCD along partly distinct pathways. This trial is registered with NTR6575.